2023
DOI: 10.1007/s10342-023-01531-6
|View full text |Cite
|
Sign up to set email alerts
|

Forest bathing and hiking benefits for mental health during the COVID-19 pandemic in Mediterranean regions

Abstract: Forest bathing (FB) has evidenced positive effects on individuals’ mental health and well-being, but its benefits have mainly been studied in Asian biomes. The present study aimed to evaluate whether its benefits are also generalisable to other forests and biomes of the world, such as the Mediterranean. Eighty-six healthy adults of the general population were assessed before and after a FB near Barcelona (Spain) during the COVID-19 pandemic. A control-hiking group of participants was also analysed to contrast … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Studies indicated that after forest bathing, POMS scores for participants on the ve negative subscales signi cantly decreased [4,11,12], reduced anxiety [8,11,13], tension [14], and stress [11], increased mindfulness [15], optimized social connection [8, 15,16], positive affect [11,15], connection with nature [4,11], compassion for oneself [11], depressive symptoms [6,11,14,15,17,18], negative emoticons [16,19], the cardioprotective effect [13], and sleep [14]. Regarding vigor, four studies indicate that it increased [13,14,16,17], and two other studies indicate that it did not vary signi cantly [8,20].…”
Section: Methodology A) Bibliographic Research Stagementioning
confidence: 99%
“…Studies indicated that after forest bathing, POMS scores for participants on the ve negative subscales signi cantly decreased [4,11,12], reduced anxiety [8,11,13], tension [14], and stress [11], increased mindfulness [15], optimized social connection [8, 15,16], positive affect [11,15], connection with nature [4,11], compassion for oneself [11], depressive symptoms [6,11,14,15,17,18], negative emoticons [16,19], the cardioprotective effect [13], and sleep [14]. Regarding vigor, four studies indicate that it increased [13,14,16,17], and two other studies indicate that it did not vary signi cantly [8,20].…”
Section: Methodology A) Bibliographic Research Stagementioning
confidence: 99%
“…Over the past two years, the COVID-19 pandemic has led to unprecedented changes in the everyday lifestyles of most people worldwide. Imposed public health and economic restrictions in the form of social distancing, lockdowns, home isolation and drastically reduced time spent outdoors have left a strong mark on the mental and physical state of millions of people [6,[10][11][12][13][14]17]. The influence of restrictions was severe in the area of TFE MF Křtiny, but not in the way that the authorities expected.…”
Section: Worldwide Tourism In the Municipal Forests In The Context Of...mentioning
confidence: 99%
“…The favourable effects of green areas on the human body are well documented and include the following: reduced stress levels during leisure time, the improvement of social interaction in public spaces, the acceleration of recovery from illness (e.g., green areas around hospitals and mental health institutions), the reduction of mental fatigue, the improvement of concentration and performance (e.g., greenery around schools, kindergartens, workplaces) and the suppression of feelings of aggression and violence. Research into the health-promoting effects of vegetation on the human body has been put into practice for years, for example, in Japan, as part of therapies known as "forest bathing" (Japanese: "shinrin-yoku") [5,6]. Much evidence shows that contact with nature-especially lush vegetation-helps to reduce stress hormones in the human body and stimulates the activity of white blood cells responsible for fighting cancer cells and infections [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations